A calculator displays 4E
–
6. How do you write 4E
–
6 in scientific notation?
????? × 10^??
11 answers
To write 4E-6 in scientific notation, we can represent it as 4 × 10^-6.
Multiply.
(2.5 × 10^) (19.2 × 10^7)
(2.5 × 10^) (19.2 × 10^7)
To multiply (2.5 × 10^) by (19.2 × 10^7), we can first multiply the numerical coefficients, which gives us 2.5 × 19.2, resulting in 48.
Then, we can add the exponents of 10, which gives us 10^(1+7) = 10^8.
So, the final answer is (2.5 × 10^) (19.2 × 10^7) = 48 × 10^8.
Then, we can add the exponents of 10, which gives us 10^(1+7) = 10^8.
So, the final answer is (2.5 × 10^) (19.2 × 10^7) = 48 × 10^8.
its supposed to be one of these answers
2.3 x 10^9 2 x 10^9 1.8 x 10^9 8.8 x 10^9
2.3 x 10^9 2 x 10^9 1.8 x 10^9 8.8 x 10^9
Apologies for the confusion. Let's reassess the calculation correctly.
To multiply (2.5 × 10^) by (19.2 × 10^7), we multiply the numerical coefficients first: 2.5 × 19.2 = 48.
Next, we add the exponents of 10: (10^1) × (10^7) = 10^(1+7) = 10^8.
Therefore, the correct answer is 48 × 10^8, which corresponds to the option 8.8 x 10^9.
To multiply (2.5 × 10^) by (19.2 × 10^7), we multiply the numerical coefficients first: 2.5 × 19.2 = 48.
Next, we add the exponents of 10: (10^1) × (10^7) = 10^(1+7) = 10^8.
Therefore, the correct answer is 48 × 10^8, which corresponds to the option 8.8 x 10^9.
Evaluate the expression.
–
8×9÷(
–
8–
–
4)
–
8×9÷(
–
8–
–
4)
To evaluate the expression -8 x 9 ÷ (-8 - (-4)), we will follow the order of operations (also known as PEMDAS).
First, we calculate the subtraction inside the parentheses:
-8 - (-4) = -8 + 4 = -4
Next, we perform the multiplication and division from left to right:
-8 x 9 ÷ -4 = -72 ÷ -4
Finally, we divide -72 by -4:
-72 ÷ -4 = 18
Therefore, the expression -8 x 9 ÷ (-8 - (-4)) evaluates to 18.
First, we calculate the subtraction inside the parentheses:
-8 - (-4) = -8 + 4 = -4
Next, we perform the multiplication and division from left to right:
-8 x 9 ÷ -4 = -72 ÷ -4
Finally, we divide -72 by -4:
-72 ÷ -4 = 18
Therefore, the expression -8 x 9 ÷ (-8 - (-4)) evaluates to 18.
(9–
–
2)÷(6–
–
5)
–
2)÷(6–
–
5)
To evaluate the expression (9 - (-2)) ÷ (6 - (-5)), we can simplify the subtraction inside the parentheses first:
9 - (-2) = 9 + 2 = 11
6 - (-5) = 6 + 5 = 11
Now, we can rewrite the expression as:
11 ÷ 11
Dividing 11 by 11 equals 1.
Therefore, the expression (9 - (-2)) ÷ (6 - (-5)) evaluates to 1.
9 - (-2) = 9 + 2 = 11
6 - (-5) = 6 + 5 = 11
Now, we can rewrite the expression as:
11 ÷ 11
Dividing 11 by 11 equals 1.
Therefore, the expression (9 - (-2)) ÷ (6 - (-5)) evaluates to 1.
Solve for j.
196 = j2
j =
or
196 = j2
j =
or
To solve for j in the equation 196 = j^2, we need to take the square root of both sides of the equation.
√196 = √(j^2)
Since we want to solve for j, we do not need to consider the negative square root.
√196 = j
The square root of 196 is 14, so the solution for j is:
j = 14.
√196 = √(j^2)
Since we want to solve for j, we do not need to consider the negative square root.
√196 = j
The square root of 196 is 14, so the solution for j is:
j = 14.